ANALISIS MODEL PEMBELAJARAN KOLABORATIF BERBASIS PERSPEKTIF GLOBAL DALAM PEMBELAJARAN IPAS PADA PESERTA DIDIK KELAS 3 - Oktaviyana, Puput Risma; Handini, Oktiani; Rizkasari, Elinda (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
Research conducted at SD Negeri 3 Jatisobo on Collaborative Learning Model Based on Global Perspective in Science Learning. Research objectives 1). Analyze the understanding of learning models 2). Implement learning. The form of research is descriptive qualitative. The object of research is science learning. Data sources were obtained from informants, namely the Principal, grade 3 teachers and six grade 3 students. Data collection using triangulation techniques The results of the study showed that after conducting interviews with grade 3 students regarding learning collaborative learning models based on global perspectives in science learning, grade 3 students of SD Negeri 2 Jatisobo, several improvements can be seen by students, including: students are more communicative in learning, more confident, skilled in linking learning with everyday life and able to discuss well. The inhibiting factors for the implementation of collaborative learning models based on global perspectives in grade 3 of SD Negeri 2 Jatisobo, namely the lack of special training on the implementation of global perspectives with an SD perspective, the habituation of students who are less active, less interaction with teachers. lack of school facilities and infrastructure to support teacher and student learning.